Analysis of the influence of design parameters of vertically-closed track conveyor with suspended belt and distributed drive on the technical specifications - Tolkachev E.N. (Научно-технический вестник Брянского государственного университета)
Using the basic design of the conveyor with suspended belt and distributed drive, a series of numerical calcu-lations was performed. As a result, the influence of design parameters of vertical loop route on the main tech-nical parameters of the conveyor was established. Recommendations on the choice of rational parameters were formulated.